Targeted SERS nanosensors measure physicochemical gradients and free energy changes in live 3D tumor spheroids. Issue 37 (12th September 2016) - Jamieson, Lauren E.; Camus, Victoria L.; Bagnaninchi, Pierre O.; Fisher, Kate M.; Stewart, Grant D.; Nailon, William H.; McLaren, Duncan B.; Harrison, David J.; Campbell, Colin J.
Abstract : Use of multicellular tumor spheroids (MTS) to investigate therapies has gained impetus because they have potential to mimic factors including zonation, hypoxia and drug-resistance. Abstract : Use of multicellular tumor spheroids (MTS) to investigate therapies has gained impetus because they have potential to mimic factors including zonation, hypoxia and drug-resistance. However, analysis remains difficult and often destroys 3D integrity. Here we report an optical technique using targeted nanosensors that allows in situ 3D mapping of redox potential gradients whilst retaining MTS morphology and function. The magnitude of the redox potential gradient can be quantified as a free energy difference (Δ G ) and used as a measurement of MTS viability. We found that by delivering different doses of radiotherapy to MTS we could correlate loss of Δ G with increasing therapeutic dose. In addition, we found that resistance to drug therapy was indicated by an increase in Δ G . This robust and reproducible technique allows interrogation of an in vitro tumor-model's bioenergetic response to therapy, indicating its potential as a tool for therapy development.